Perbandingan Pendapatan Usahatani Kentang Varietas Granola L dan Super John di Kecamatan Passi Timur Kabupaten Bolaang Mongondow - Rakian, Sanly Veronica; Laoh, Olly Esry Harryani; Jocom, Sherly Gladys (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2025)
The objective of this study is to analyze the income comparison between potato farmers cultivating Granola L and Super John varieties in Passi Timur District. The research employed a Simple Random Sampling method with 60 farmer respondents, consisting of 30 Granola L farmers and 30 Super John farmers. The variables examined in this study include production, price, and production costs. Income comparison was conducted using an independent samples t-test with SPSS software, based on the average income per hectare of Granola L and Super John farmers. The results show that Granola L farmers achieved an average production of 12,602.24 kg/ha with an average selling price of IDR 9,166.67/kg, resulting in an income of IDR 80,019,440.63/ha. Meanwhile, Super John farmers recorded an average production of 11,586.01 kg/ha with an average selling price of IDR 8,916.67/kg, yielding an income of IDR 71,803,381.17/ha. The income comparison between the two farming systems was further analyzed using the t-test, which produced a significance value (2-tailed) of 0.555 > 0.05. Thus, the null hypothesis (H0) is accepted and the alternative hypothesis (H1) is rejected. This indicates that there is no significant difference in income between Granola L and Super John potato farming.